Processamento de bebida gaseificada a partir do soro de leite caprino - Araújo, Luiz Fernando da Silva (2023)
This work involved formulating a carbonated drink, using whey from goat's milk, obtained from the manufacture of coalho cheeses, with the purpose of evaluating its shelf life. Six treatments were carried out: Control, Guarana, Orange, Lemon, Grape and Cashew. Stability was periodically evaluated by microbiological and physical-chemical analyses, followed by sensory analysis, approved by the Human Research Ethics Board of the Health Sciences Center of UFPB. The physicochemical characterization showed the average composition during the four weeks: Control, proteins 0.96%, pH 3.87, brix 10.45%; Guarana, proteins 0.93%, pH 3.70, brix 14.60%; Orange, proteins 0.91%, pH 3.52, brix 12.90%; Lemon, proteins 0.94%, pH 3.70, brix 12.75%; Grape proteins 0.97%, pH 3.77, brix 13.40%; Cashew, proteins 0.87, pH 3.87, brix 13.35%. In the microbiological characterization, coliform counts were observed at 35 ºC and 45 ºC (3< MPN/mL), with no observations of typical colonies of coagulase-positive Staphylococci and Salmonella spp. The sensory analysis by ordering, the Lemon treatment presented the most acidic taste and difference between the treatments. The results showed stability for 21 days under refrigeration at 2 °C. The use of whey from goat milk to prepare carbonated drinks appears as a viable alternative